Differences in muscle activity and intermuscular coordination between dominant and non-dominant hands during chopstick manipulation - Komi, Hina; Kurumadani, Hiroshi; Kurauchi, Kazuya; Date, Shota; Sunagawa, Toru (Frontiers in Human Neuroscience, 2025)
IntroductionTo develop an efficient rehabilitation program for patients with stroke to acquire fine motor skills such as chopstick manipulation, it is necessary to examine the differences in fundamental muscle functions between the hands during motor tasks. The aim of this study was to clarify the differences in muscle activity and intermuscular coordination between dominant and non-dominant hands during chopstick manipulation.MethodsTwenty-eight healthy adults performed the task of picking up different-sized objects using chopsticks with either their dominant or non-dominant hand. Surface electromyography of 11 intrinsic and extrinsic hand muscles was performed, and muscle activity and muscle activity waveforms during the task were calculated. Activity patterns and weighting for each pattern were extracted from the muscle activity waveforms using non-negative matrix factorization to represent muscle synergy. The muscle activity and weighting were compared between the dominant and non-dominant hands and among different-sized objects.ResultsThe activities of most intrinsic and extrinsic muscles did not significantly differ between the dominant and non-dominant hands or among different-sized objects. Although activity patterns showed the coordination of intrinsic hand muscles in both the dominant and non-dominant hands, the combinations of the weighting differed between the dominant and non-dominant hands. The non-dominant hand had different muscle activation patterns of intrinsic and extrinsic hand muscles compared to the dominant hand. The activity patterns and weighting were mostly similar across different-sized objects.ConclusionThe dominant hand showed coordination of the first and second lumbrical muscles, whereas the non-dominant hand showed no muscle activation patterns between the muscles. Therefore, it is important to emphasize the first and second lumbrical in the non-dominant hand during rehabilitation to improve the coordination between the muscles of the two hands during chopstick manipulation to effectively improve chopstick manipulation skills in the non-dominant hand.